2020
DOI: 10.1016/j.ijscr.2020.11.106
|View full text |Cite
|
Sign up to set email alerts
|

The strategy for Mirizzi syndrome type II with laparoscopic surgery: A case report

Abstract: Highlights Mirrizi syndrome is a inflammation to the common bile duct. Open surgery is usually recommended for Mirrizi syndrome types II-IV. We treated with laparoscopic surgery and describe the utility of laparoscopic surgery for Mirrizi syndrome type Ⅱ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…We consider that LC including RPS for Mirizzi syndrome can be performed safely when a tailored therapeutic strategy appropriate to the state of the disease is planned properly. Sato et al reported that laparoscopic partial resection of the gallbladder can be safely performed as planned based on precise preoperative diagnosis using various modalities, including ERCP 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that LC including RPS for Mirizzi syndrome can be performed safely when a tailored therapeutic strategy appropriate to the state of the disease is planned properly. Sato et al reported that laparoscopic partial resection of the gallbladder can be safely performed as planned based on precise preoperative diagnosis using various modalities, including ERCP 4 …”
Section: Discussionmentioning
confidence: 99%
“…Sato et al reported that laparoscopic partial resection of the gallbladder can be safely performed as planned based on precise preoperative diagnosis using various modalities, including ERCP. 4 As described, a suitable surgical procedure should be selected depending on its subtype to avoid intraoperative biliary injury and/or postoperative bile leakage. The contemplated guideline, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It means that in these cases, LSRC is effective to treat MSII y III. LSRC, as laparoscopic subtotal “fenestrating” cholecystectomy, had recently been proposed as safe (without biliary injury) and effective (single surgery to solve MS) techniques for difficult operative conditions [3] , [4] , [12] , [13] . There are no studies comparing both techniques in MS Type II & III, but evidence show both procedures prevents conversion and has fewer serious complications [14] , [15] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…According to Csendes, MS type II and III are categorized as a fistula of one third and two thirds of the common hepatic duct circumference, respectively [1] . The difficulty to confirm the diagnosis before surgery, the technical challenge due to the severe inflammatory reaction, the difficult identification of normal structures, the need for advance laparoscopic technics to perform a successful surgery and the absence of evidence on the best surgical technique determines a high rate of conversion, reoperation, and risk bile duct injury [2] , [3] , [4] . This case series shows the outcomes of mexican patients who underwent laparoscopic subtotal reconstitutive cholecystectomy (LSRC) for type II and III MS with the aim of determining whether the procedure can be a safe and effective approach in our institution.…”
Section: Introductionmentioning
confidence: 99%